Advances in Piezoelectric Polymer Composites for Energy Harvesting Applications: A Systematic Review. Issue 1 (27th November 2018) - Mishra, Suvrajyoti; Unnikrishnan, Lakshmi; Nayak, Sanjay Kumar; Mohanty, Smita
Abstract: Polymeric piezoelectric composites for energy harvesting applications are considered a significant research field which provides the convenience of mechanical flexibility, suitable voltage with sufficient power output, lower manufacturing cost, and rapid processing compared to ceramic‐based composites. This review focuses majorly on the basic theory and principles behind piezoelectric energy harvesting (PEH) devices, followed by specified materials used for the different devices. Different structural configurations associated with fabrication of PEH devices are discussed in detail along with their major advantages and drawbacks. Numerous classes of piezoelectric polymers such as polyvinylidene fluoride, polylactic acid, cellulose, polyamides, polyurea, polyurethanes, and their composites used for energy harvesting applications as a productive alternative of lead‐based piezo‐ceramics, are extensively addressed and explored. Additionally, current global and Indian scenarios associated with PEH devices, major challenges associated with them, and the future perspective of such devices are also reported in this review. Abstract : The versatility of different piezoelectric materials for energy harvesting applications is explored throughout this review while giving special attention to piezoelectric polymers and composites. It has been revealed that these materials could be a better alternative to piezo‐ceramics, in terms of mechanical flexibility, suitable voltage with sufficient power output, lower manufacturing cost, and rapid processing.